Thermal Characteristics of Epoxy Fire-Retardant Coatings under Different Fire Regimes - Marina Gravit; Daria Shabunina; Nikita Shcheglov (Fire, 2023)
Different systems of fire protection coatings are used to protect the metal structures of stories and trestles at oil and gas facilities from low (when filling cryogenic liquids) and high temperatures (in case of the possible development of a hydrocarbon fire regime). This paper presents the results of experiments of fireproof coatings on an epoxy binder after the simulation of a liquefied hydrocarbons spill and subsequent development of a hydrocarbon fire regime at the object of protection and exposure of structures to a standard fire regime. According to the experimental results, the temperatures on the samples at the end of the cryogenic exposure were determined and the time from the beginning of the thermal exposure to the limit state of the samples at a hydrocarbon and standard temperature fire regime was determined. As a result, temperature–time curves in the hydrocarbon and standard fire regimes were obtained, showing good convergence with the simulation results. The solution of the inverse task of heat conduction using finite element modeling made it possible to determine the thermophysical properties of the formed foam coke at the end of the fire tests of steel structures with intumescent coatings. It was determined that an average of 12 mm of intumescent coating thickness is required to achieve a fire protection efficiency of 120 min and for the expected impact of the hydrocarbon fire regime, the coating consumption should be increased by 1.5–2 times compared to the coating consumption for the standard regime.